(3GdbUjOI GdeaMeI HJaSjQgGs - (3eMeO Hf GdMSf Hf eMeO Hf YHO Gddg GdcdGYj GdMejQj GdjeGfjs ((3Ydi Hf RjO Hf CMeO Hf jMji s)
(3ChdgG (B:s
(3Ndjdi gd QHY HMaGK ebaQ Pi GdLhG Ch jNHQ s
(3BNQgG (B:s
(3hYfOi CeKGd dgG dGJZQfi hZjQi jYei Ohf PGc hjMUQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3GdfSNI HgG MhGTs
(3hgj ai (B312 (3HjJkGs
(3hGdeDda eMeO Hf GdMSf GdcdGYi s
(3jLjH HgG GdaVd Hf JGQOL GdQhei s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdCOHs